Frenzone Enterprise - Frankie, Janet; Galasun, Nora; Morise, Doress; Nordin, Nuralinah Shakinah; Mohd Nadzri, Nur Ashyikin (2014)
FrenZone Enterprise is a form of business that produces variety types of product by using reusable or recycling products. Products that we produce are toys, for example: cars, boat, and airplanes. Other than toys, we also produce products where all parents also can enjoy the benefit of these products. For instance like mini vacuum, mousetrap and many more. FrenZone Enterprise is located at (KK area). As we know that children loves to play toys and here we came out with an incredible ideas to make our own toys. FrenZone Enterprise is the one and only enterprise whom came out with this creative invention and innovation. We know that some of the children just love toys so much and they would not care about either the toys was being invented by using a high technology or just by using simple method or technique as long as the toys are fun. We, FrenZone Enterprise saw the opportunity that this business not only helps all children to have their own simple and cool toys as well as our business can help to reduce the amount of rubbish in the Kota Kinabalu area.